Puentes entre conocimientos tradicionales y conocimientos científicos escolares con relación a las plantas medicinales en el grado 8vo del liceo Nuestra Señora de Torcoroma - Páez-Rincón, Duberney; Reyes-Roncancio, Jaime Duvan (Revista Científica, 2020)
The current educational dynamics and the conception of science as a cultural system make evident the need to generate new perspectives for teaching biological content, abandoning traditional training processes which focus on thematic content. This article brings together the results of an investigation into the implementation of didactic activities that allowed the identification of the bridges between traditional knowledge TC and scientific knowledge CCE school around the teaching of the medicinal properties of plants in grade 8 of our high school nuestra señora del Torcoroma. In the development of this work, a body of school knowledge was found that relates the use of 17 plant species as a treatment mechanism for 15 common conditions, in the same way a categorization of the bridges between knowledge is proposed based on the positions of science that They show the students and the validity criteria they assume for scientific and traditional knowledge, allowing to identify: disruptive bridges that are described as relationships between TC and CCE that generate hierarchy and non-validation of traditional knowledge; Assimilation bridges that allow the TC to be recognized but not give it a valid status as that of the CCE and Integrative bridges that validate the CT and link it to the CCE to generate holistic knowledge. These results frame students as generators of dialogue of knowledge and as builders of school knowledge, which makes evident the need to generate teaching proposals that dignify the knowledge of social groups and recognize science as a body of cultural and epistemological diversity.